2016
DOI: 10.1017/s0031182016000962
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Bartonella genotypes found in the striped field mouse (Apodemus agrarius) in Central Europe

Abstract: We investigated the diversity of Bartonella in Apodemus agrarius, an important rodent of peri-domestic habitats, which has spread into Europe in the past 1000 years. Spleen samples of 344 A. agrarius from Eastern Slovakia were screened for the presence of Bartonella spp. using 16S-23S rRNA internal transcribed spacer region and bacteria were detected in 9% of rodents. Based on sequencing of three housekeeping genes (gltA, rpoB and groEL) Bartonella genotypes were ascribed to the species typical for mice and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
6
21
0
Order By: Relevance
“…Sixteen individuals (9.35%) (nine from Taterillus sp., four from A. niloticus, and three from M. erythroleucus) were positive. This global prevalence is particularly similar to those previously reported 9%) [40]. Diagne et al [19] previously reported Bartonella spp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sixteen individuals (9.35%) (nine from Taterillus sp., four from A. niloticus, and three from M. erythroleucus) were positive. This global prevalence is particularly similar to those previously reported 9%) [40]. Diagne et al [19] previously reported Bartonella spp.…”
Section: Discussionsupporting
confidence: 91%
“…Among those known to be potentially zoonotic, we can cite B. tribocorum, B. grahamii, B. elizabethae, B. vinsonii subsp. arupensis, B. washoensis, and B. alsatica [40]. In addition, in rodents' ectoparasites, a high prevalence of zoonotic bartonellosis agents were found (43.75% of B. elizabethae in Stenoponia tripectinata tripectinata) [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen individuals (9.35%) (9 from Taterillus sp., 4 from A. niloticus and 3 from M. erythroleucus) were positive. This global prevalence is particularly similar to those previously reported 9%) [32]. Diagne et al [19] Several studies showed different genotypes of the same species [32] or even new species [19].…”
Section: B) Molecular Screeningsupporting
confidence: 90%
“…This global prevalence is particularly similar to those previously reported 9%) [32]. Diagne et al [19] Several studies showed different genotypes of the same species [32] or even new species [19]. [48] and previous studies have reported a high prevalence of Anaplasmataceae in rodents [7] in Senegal [20].…”
Section: B) Molecular Screeningsupporting
confidence: 89%